A machine learning-aided multi-objective optimisation decision support framework for the healthcare social enterprise location problem - Jacobs, Rentia (Stellenbosch : Stellenbosch University, 2025)
Jacobs, R. 2025. A machine learning-aided multi-objective optimisation decision support framework for the healthcare social enterprise location problem. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/f6550db7-f565-4b1b-985b-b896b305b7fb